Twenty-First-Century Antigones : The Postcolonial Woman Shaped by 9/11 in Kamila Shamsie's Home Fire - Mendes, Ana Cristina Ferreira (2021)
Set in the early 2010s, the backdrop of Kamila Shamsie's novel Home Fire (2017) is a familiar one to contemporary readers, colored by the rise of far-right populist movements and the increase in anti-Muslim initiatives. This article examines how the novel engages with new Orientalist representations post-9/11 on two levels. Firstly, Shamsie's novel is shaped by the political narratives of the War on Terror and, in turn, responds to the upshot of these new configurations of power, reflecting how the difficulty of making sense of 9/11 exacerbated the Orientalist binary of East and West. Secondly, the novel reflects on the unenviable choice, for female kin to male terrorists, of either being Orientalized or re-orientalizing, a form of self-perpetrated Othering. This study is framed by re-orientalism theory in its analysis of how the East continues to engage the West in increasingly self-aware, multi-layered ways, constantly renegotiating positions of power and influence.